Characterization of a novel HMG-CoA lyase enzyme with a dual location in endoplasmic reticulum and cytosol - Arnedo, María (2012)
A novel lyase activity enzyme is characterized for the first time: HMG-CoA lyase-like1 (er-cHL), which is a close homolog of mitochondrial HMG-CoA lyase (mHL). Initial data show that there are nine mature transcripts for the novel gene HMGCLL1, although none of them has all its exons. The most abundant transcript is called "variant b," and it lacks exons 2 and 3. Moreover, a three-dimensional model of the novel enzyme is proposed. Colocalization studies show a dual location of the er-cHL in the endoplasmic reticulum (ER) and cytosol, but not in mitochondria or peroxisomes. Furthermore, the dissociation experiment suggests that it is a nonendoplasmic reticulum integral membrane protein. The kinetic parameters of er-cHL indicate that it has a lower Vmax and a higher substrate affinity than mHL. Protein expression and lyase activity were found in several tissues, and were particularly strong in lung and kidney. The occurrence of er-cHL in brain is surprising, as mHL has not been found there. Although mHL activity is clearly associated with energy metabolism, the results suggest that er-cHL is more closely related to another metabolic function, mostly at the pulmonary and brain level.